MODEL OF ETHNONATIONAL VICTIMIZATION OF THE POPULATION OF UKRAINE ON THE EXAMPLE OF THE KHERSON REGION - D. V. Makovskaya; L. N. Garas (Современная наука и инновации)
The article is devoted to the study of the role of ethno-national victimization of the Ukrainian population as a means of constructing a civil identity and implementing foreign policy strategies.